(untitled) (Historia, 2021)
Murderers, Miscreants and Mutineers marks the long awaited and much anticipated sequel to Nigel Penn’s popular Rogues, Rebels and Runaways, published in 1999. There is an important caveat, however, for those who are familiar with Penn’s canon over the past fifteen-odd years: five of the six chapters that appear in the work have been published before as journal articles. Even so, it is pleasing that the story of Johannes Seidenfaden - rogue missionary extraordinaire - has finally seen the light of day in chapter 6, which marks his first published appearance. By bringing this collection together between the same covers, the author has provided a useful means by which to reflect on the state of Cape history and the ways in which the field has evolved since the publication of Rogues, Rebels and Runaways.